Duodenal Gastrointestinal Stromal Tumor - Divya Teja Patil; Anil Kumar Sakalecha; Parameshwar Keerthi B.H; Yashas Ullas L (Journal of Clinical and Biomedical Sciences)
Gastrointestinal stromal tumors (GIST) are nonepithelial tumors arising from the interstitial cells of Cajal. They express KIT protein-CD117 on immunohistochemistry. GIST can arise anywhere in the GIT, including the mesentery, omentum, and ret-roperitoneum. In the duodenum, 2nd or 3rd part of duodenum is the most common site. Imatinib is the drug of choice and sur-gical resection is the main modality of treatment. Keywords: Gastrointestinal Stromal Tumor